Designing and Implementing a Database for Thesis Data Management by Using the Python Flask Framework - Suraya, Suraya; Sholeh, Muhammad (Malikussaleh University, Aceh, Indonesia, 2022)
This study aims to implement the database design used in thesis data processing using Flask. The results of the database design produce four tables, namely the lecturer table is used to store lecturer data, the student table is used to store student data, the title of thesis table is used to store data related to student thesis and the guidance table contains history during guidance with the supervisor, The design of the thesis data processing database was developed using Flask. Flask is a web framework written in Python. Flask serves as the application framework and the interface of the web-based flask application. In this research, the methodology used is to implement database development which consists of system analysis, logical design, physical design and implementation. The database design methodology is carried out by 1. Building a local conceptual data design based on user views, 2. Building and validating local logical data models, 3. Building and validating logical data models, 4. Translating logical data models for the database management system, 5. Designing and implementation of physical representation. The results show that the process of creating a thesis data management database can be done using the Flask framework. The development process using the flask framework includes the process of creating databases, tables and reading, adding, repairing and deleting data. In making the application, the application is divided into 2, namely the application used for database management and the application used to display website-based results that are used to display the results of data processing from the application. Implementation of data structures in the database design and applications used include programming language: Python 3.7.0, framework for displaying web-based data: Flask 1.1.2, and database management system using SQLite.